2018
DOI: 10.1002/ppsc.201700387
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Visualization of Latent Fingerprints with Color‐Tunable Solid Fluorescent Carbon Dots

Abstract: Latent fingerprints (LFPs) imaging is the most important approach to identify individuals, and there is a persisting need for the development of simple, rapid, accurate, and universal LFPs recognition methods. The nitrogen‐ and sulfur‐doped solid fluorescent carbon dots (N,S‐SFCD) are synthesized with a simple microwave‐assisted method by using l‐glutathione and citric acid as precursors. The obtained N,S‐SFCD has a uniform size from 2 to 7 nm with quantum yield over 48%. The presence of heteroatoms and functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 48 publications
0
31
0
1
Order By: Relevance
“…Two research groups reported the use of a powder containing only C‐dots (G. Ren et al, ; C. Wang, Zhou, et al, ). Sebaceous‐rich fingermarks were successfully detected on silicon wafers (G. Ren, Meng, et al, ).…”
Section: Carbon Dotsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two research groups reported the use of a powder containing only C‐dots (G. Ren et al, ; C. Wang, Zhou, et al, ). Sebaceous‐rich fingermarks were successfully detected on silicon wafers (G. Ren, Meng, et al, ).…”
Section: Carbon Dotsmentioning
confidence: 99%
“…Instead of immersing the substrate into a solution, two different groups tried to spray the C‐dots (J. Chen et al, ; C. Wang, Zhou, et al, ). Chen et al used red‐emitting C‐dots in a 0.1 M hydrochloric acid solution (J. Chen, Wei, et al, ).…”
Section: Carbon Dotsmentioning
confidence: 99%
See 1 more Smart Citation
“…5,8,9 The photoluminescence detection of LFPs is considered to be a more effective approach due to its higher selectivity and contrast than traditional methods such as iodine fuming and vacuum metal deposition. 10,11 Many photoluminescent probe candidates have been reported for LFP imaging, such as conjugated polymer nanoparticles, 12,13 nanophosphors, 14 organic aggregation-induced emission uorophores, 4,15 noble metal nanoclusters, [16][17][18] semiconductor quantum dots, 8,19 and rare earth upconversion uorescent nanomaterials. 20,21 However, these materials suffer from some shortcomings; for example, using noble metals increases the cost of the photoluminescent probes.…”
Section: Introductionmentioning
confidence: 99%
“…14,34 The resolution and contrast of imaging can be enhanced by using organic matter such as coumarin A with functional groups that generate electrostatic interactions to adhere the LFPs on the surface of the uorescent powder. 4,5,8,22 Herein, we successfully designed and synthesized a LFP probe by using a simple organic-inorganic hybrid strategy to combine the inorganic aerglow phosphor SrGa 12 O 19 :Mn 2+ (SGO:Mn) and ethyl cellulose (EC). SGO is a superior aerglow host lattice, as reported in our previous works, and the proper crystal eld environment for Mn 2+ ions' narrow band emitting can be provided by the SGO host.…”
Section: Introductionmentioning
confidence: 99%